Optimization of water yield, carbon storage and wood production in forest planning by mixed integer programming - Değermenci, Ahmet Salih; Zengin, Hayati; Ünal, Murat Engin (BOSQUE, 2022)
Interventions to the forest also affect the amount and quality of water and carbon storage; revenues to be obtained from these areas as well. Therefore, for the long-term estimation of the harvest plans to be organized, it is necessary to eliminate the lack of information for other functions provided by the forests and to quantify their relationship with forest dynamics. In this study, it was intended to determine how forest functions, such as wood production, hydrologic and carbon storage functions, changed according to different objective functions and constraints and what kind of harvest scheduling is prepared in line with a planning process. Seven different planning strategies have been developed for the Çiçekli planning unit, aimed at maximizing profit according to these different strategies. Among the developed strategies, the highest objective function value (500,704,847 TL) was obtained in the strategy 6 (ST6), where there is no Optimal Periodic Area (OPA) constraints. The highest amount of water (894,728,400 m3) was obtained in the strategy 7 (ST7), which has a constraint on the amount of area to be regenerated. While the amount of carbon stored in the planning unit decreased due to the high amount of regenerated area in most planning strategies, only in ST7 it has increased in all periods, showing periodic regeneration constraints. At the end of the planning horizon, the amount of growing stock (2,446,402 m3) has increased only in ST7 with regeneration constraints, whereas the amount of growing stock has decreased in all other strategies.